The Movement of Sundanese Karawitan Artist in the Indie Music From the Perspectiv of Music Sociology - Saputra, Firman Adi; Saleh, Sukmawati (Pascasarjana ISBI Bandung, 2024)
This research delves into the attitudes and perspectives of Sundanese karawitan artists toward the indie music movement through the lens of music sociology. Employing qualitative methodologies such as literature review and fieldwork, the study reveals that these artists do not merely act as preservers of cultural heritage but also actively adapt and integrate their traditional music into the indie music scene. As pivotal figures, they engage in collaborations with global elements within the indie world, making substantial contributions to the evolution of indie music. This active participation fosters a unique harmony that mirrors the diverse and dynamic nature of Indonesian culture. The study offers a comprehensive analysis of how Sundanese karawitan artists interact with and influence the indie music scene. Their involvement is not just a preservation of traditional art forms but a dynamic adaptation that enriches both their cultural heritage and the broader indie music movement. By blending traditional and contemporary elements, these artists create innovative music that appeals to a global audience while retaining its cultural roots. Furthermore, this research highlights the significant role of Sundanese karawitan artists in the indie music scene, showcasing their ability to navigate between tradition and modernity. Their contributions reflect a broader trend in the Indonesian music landscape where traditional art forms are not static but are continually evolving and adapting to new contexts and influences. This dynamic interplay between tradition and innovation is crucial for the sustainability and growth of both traditional and indie music genres in Indonesia.